Mental Training for Better Achievement: Effects of Verbal Suggestions and Evaluation (of Effectiveness) on Cognitive Performance - Fuhr, Kristina; Werle, Dustin (Frontiers in Psychiatry, 2018)
Objective: The influence of expectations and suggestions on cognitive performance was previously investigated in the context of consuming different substances (including placebos). For example, cognitive performance improved after suggesting participants they had consumed caffeine similar to the improvement after they really consumed caffeine. Comparable results were found when college students believed that they had received a “neuro-enhancing” stimulant. However, enhancing cognitive performance only via verbal suggestions has not yet been examined. The goal of our study was therefore to investigate the effects of a mental training based on verbal suggestions compared to a control training on cognitive performance in a student population using a balanced-placebo-design. Methods: In total, 103 participants were randomly assigned either to listening to a 20 minutes audio-taped mental training or to a 20 minutes philosophy lecture (control training) via headphones. Participants were individually tested before and after the training concerning their cognitive performance. Information about the type of training were varied in both intervention conditions („You are part of our experimental condition and you will receive an effective mental training“ or „You are part of our control group and you will receive the control condition“). The effects of these four conditions on cognitive performance were tested. At the end of the assessment, participants were asked what kind of training they believed they had received and how effective they would rate the received training. Results: Overall, the cognitive performance improved in all participants. Contrary to our hypotheses, we found no interaction or main effects of the type of training and type of instruction on the cognitive performance. However, the cognitive performance significantly improved more when participants rated their training as being effective. Conclusion: The subjects’ own believes and expectations might play a more important role for their cognitive performance than the actual training or the information they receive regarding the type of training. Thus, expectations have a large impact on the efficacy of a specific training. This finding underlines the relevance of enhancing the self-efficacy in situations where cognitive attention processes are important and of individually tailoring mental trainings.